If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6y + 10 = 6y + 26 Reorder the terms: 10 + -6y = 6y + 26 Reorder the terms: 10 + -6y = 26 + 6y Solving 10 + -6y = 26 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. 10 + -6y + -6y = 26 + 6y + -6y Combine like terms: -6y + -6y = -12y 10 + -12y = 26 + 6y + -6y Combine like terms: 6y + -6y = 0 10 + -12y = 26 + 0 10 + -12y = 26 Add '-10' to each side of the equation. 10 + -10 + -12y = 26 + -10 Combine like terms: 10 + -10 = 0 0 + -12y = 26 + -10 -12y = 26 + -10 Combine like terms: 26 + -10 = 16 -12y = 16 Divide each side by '-12'. y = -1.333333333 Simplifying y = -1.333333333
| T=2π√(l/9) | | 6S=228 | | -3x/2 | | (z-1)(2z-7)=0 | | 7+12x=163 | | 3xb+2a+1=-4 | | 7+12x=160 | | -5=-7/y-4 | | Fg(0)= | | 5h+25=3h+30.76 | | 17-2a=5 | | 12x+7=144 | | 2k-7k/2=3/4 | | (3z-4)^2/3=(16z)1/3 | | 4x+x-2x+3=23 | | 5-3xa=-4 | | 2*.5+3x=1 | | 12x+7=156 | | 2x+y+z=3x+y | | 8-(-12)= | | -7x^2+2x-6=0 | | 24+3t=1.50t | | 9ln(x-14)-4ln(x)= | | 3*3*3*y=24 | | t^4-4t^2+4=0 | | 4x^2+5y^2-32x+60y+224=0 | | A=Bh/3 | | 9m^2+3m-6=0 | | 0.35x+0.10(100-x)=28 | | -x^7=40 | | 0.35x+10(100-x)=28 | | 0.35x+10(100-x)=8 |